2019
DOI: 10.1158/1541-7786.mcr-19-0147
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Peripheral Nerve Sheath Tumors: From Epigenome to Bedside

Abstract: Malignant peripheral nerve sheath tumors (MPNST) are aggressive sarcomas typically developing in the context of neurofibromatosis type 1 (NF-1). With the exception of surgical resection, these tumors are resistant to all current therapies, and unresectable, recurrent, or metastatic tumors are considered incurable. Preclinical studies have identified several novel candidate molecular targets for therapeutic intervention, but, to date, targeted therapies have proven ineffective. Recent studies have identified re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(76 citation statements)
references
References 160 publications
2
68
0
6
Order By: Relevance
“…MPNSTs can develop sporadically (50%), most commonly in middle to advanced aged patients, or in association with NF1, a neurological cancer predisposition syndrome [38]. NF1 is an autosomal dominant condition that occurs through germline loss-of-function mutation of the neurofibromin 1 gene (NF1), which as noted above ultimately results in hyperactivation of Ras [77]. NF1 patients display a mosaic of clinical manifestations, most notably including the development of benign lesions called neurofibromas (NFs).…”
Section: Malignant Peripheral Nerve Sheath Tumors (Mpnsts)mentioning
confidence: 99%
See 2 more Smart Citations
“…MPNSTs can develop sporadically (50%), most commonly in middle to advanced aged patients, or in association with NF1, a neurological cancer predisposition syndrome [38]. NF1 is an autosomal dominant condition that occurs through germline loss-of-function mutation of the neurofibromin 1 gene (NF1), which as noted above ultimately results in hyperactivation of Ras [77]. NF1 patients display a mosaic of clinical manifestations, most notably including the development of benign lesions called neurofibromas (NFs).…”
Section: Malignant Peripheral Nerve Sheath Tumors (Mpnsts)mentioning
confidence: 99%
“…Both sporadic and NF1-associated MPNSTs have complex karyotypes characterized by NF1-inactivating mutations along with frequent genetic disruptions of CDKN2A and polycomb repressor complex-2 (PRC2) components, SUZ12 or EED [78,80]. Inactivation of PRC2, which causes loss of histone H3 lysine 27 (H3K27) tri-methylation and global changes in gene expression, is a marker of poor survival in MPNST [77]. Normally, PRC2 transcriptionally represses several genes in the CDK pathway, including CDKN2A and the genes encoding cyclins D1 and E1, CCND1 and CCNE1 [81].…”
Section: Malignant Peripheral Nerve Sheath Tumors (Mpnsts)mentioning
confidence: 99%
See 1 more Smart Citation
“…Not surprisingly, the consequences of PRC2 loss on the oncogenic signaling within the MPNST cell has become an intensive area of investigation in the NF1 research community. The current paradigm proposes a combination of H3K27me3 loss and de-repression of PRC2 target genes along with other consequential epigenetic alterations in the chromatin landscape promoting oncogenesis [108]. However, it remains unclear exactly what arethe MPNST specific PRC2 target genes that are de-repressed as the malignant transformation takes place.…”
Section: Consequences Of Prc2 Loss On Oncogenic Signaling In Mpnstmentioning
confidence: 99%
“…These include molecular variants of the NF1 tumor suppressor gene that are present in all NF1 patients, and in a majority of sporadic and radiation-induced MPNSTs (2,3). Other ancillary, yet essential, cancer-driving genetic aberrations include loss of the genes CDKN2A, TP53, RB, or PTEN, or the genes encoding the PRC2 components SUZ12 or EED, and amplification of PDGFRA, EGFR, or MET (4,5). In addition, recent studies have shown that activation of multiple signaling pathways, including the PI3K/AKT/mTOR, RAS/RAF-MEK-ERK, Wnt/β-catenin, and HIPPO-YAP/TAZ pathways, and other less ubiquitous molecular alterations involving aurora kinases and transcription factors (TFs) such as SOX9, also contribute to MPNST pathogenesis (1,3,6).…”
Section: Introductionmentioning
confidence: 99%